Role of deubiquitinating enzymes in DNA double-strand break repair - LI, Yunhui (J Zhejiang Univ Sci B, 2021)
DNA is the hereditary material in humans and almost all other organisms. It is essential for maintaining accurate transmission of genetic information. In the life cycle, DNA replication, cell division, or genome damage, including that caused by endogenous and exogenous agents, may cause DNA aberrations. Of all forms of DNA damage, DNA double-strand breaks (DSBs) are the most serious. If the repair function is defective, DNA damage may cause gene mutation, genome instability, and cell chromosome loss, which in turn can even lead to tumorigenesis. DNA damage can be repaired through multiple mechanisms. Homologous recombination (HR) and non-homologous end joining (NHEJ) are the two main repair mechanisms for DNA DSBs. Increasing amounts of evidence reveal that protein modifications play an essential role in DNA damage repair. Protein deubiquitination is a vital post-translational modification which removes ubiquitin molecules or polyubiquitinated chains from substrates in order to reverse the ubiquitination reaction. This review discusses the role of deubiquitinating enzymes (DUBs) in repairing DNA DSBs. Exploring the molecular mechanisms of DUB regulation in DSB repair will provide new insights to combat human diseases and develop novel therapeutic approaches.